ParaFrag - an approach for surface-based similarity comparison of molecular fragments - Jakobi, Arjen-Joachim; Mauser, Harald; Clark, Timothy (Journal of Molecular Modeling, 2008)
A frequent task in computer-aided drug design is to identify novel chemotypes similar in activity but structurally different to a given reference structure. Here we report the development of a novel method for atom-independent similarity comparison of molecular fragments (substructures of drug-like molecules). The fragments are characterized by their local surface properties coded in the form of 3D pharmacophores. As surface properties, we used the electrostatic potential (MEP), the local ionization energy (IEL), local electron affinity (EA(L)) and local polarizability (POL) calculated on isodensity surfaces. A molecular fragment can then be represented by a minimal set of extremes for each surface property. We defined a tolerance sphere for each of these extremes, thus allowing us to assess the similarity of fragments in an analogous manner to classical pharmacophore comparison. As a first application of this method we focused on comparing rigid fragments suitable for scaffold hopping. A retrospective analysis of successful scaffold hopping reported for Factor Xa inhibitors [Wood MR et al (2006) J Med Chem 49:1231] showed that our method performs well where atom-based similarity metrics fail.
Keywords: fragment; molecular surface; similarity searching; scaffold hopping; pharmacophore matching